Good Corporate Governance dan Penerapannya di Perbankan Syariah - Sri Wahyuni (MES Bogor, 2023)
Good Corporate Governance is a set of laws, rules and regulations that must be followed; can also encourage the performance of business resources to function effectively in order to provide long-term economic benefits for shareholders and the surrounding community. This investigation is a type of field research. Adam Malik from Bank Syariah Indonesia KCP Medan conducted this research. Secondary data is a source of information used. Observation and interviews are one of the data collection techniques used by researchers. The conclusions that can be drawn based on the findings of hypothesis testing and referring to the formulation and objectives of the study: The profitability of Islamic banking is positively and significantly influenced by the quality of GCG implementation. According to research findings, GCG has a good and quite large influence on the profitability of Islamic banking. So that there is a positive relationship because the greater the GCG score, the better the performance, and the healthier the bank, the better the relationship. Good corporate governance (GCG) that is not implemented consistently has an impact on the bank's financial performance.